Parallel in vivo and in vitro Studies of the Incorporation of P32 in the Phospholipids of Leukemic Leukocytes - Miras, C.; Samara, V.; Mantzos, J. (Nuklearmedizin - NuclearMedicine, 1963)
The incorporation of radioactivity from orthophosphate-P32 in leukocyte phospholipids has been examined in vivo and in vitro in patients with leukaemia. Blood taken before the administration of a therapeutic dose of P32 was incubated with amount of P32 equal to that found in circulation 30 minutes following the intravenous injection of the therapeutic dose.The distribution of radioactivity found 6 hours later in the phospholipid fraction of leukocytes in patients treated with P32 was examined. At the same time, the incorporation of radioactivity from P32 in the leukocyte phospholipids (cephalin, lecithin, sphingomyelin), taken from the same subject and kept during this time under incubation, was compared to the values observed in vivo.A fairly good agreement between the in vivo and in vitro distribution in the main fractions of leukocyte phospholipids was found in these experiments.L’introduction de la radioactivité de l’orthophosphate P32 dans les phos-pholipides des leucocytes a été étudiée in vitro et in vivo chez des malades souffrants d’une leucémie. Des échantillons de sang pris avant l’application de P32 ont été incubés avec une quantité de P32 égale à celle qui se trouvait dans la circulation du sang 30 minutes après l’injection intraveineuse de la dose thérapeutique. La distribution de la radioactivité dans la fraction phospho-lipide des leucocytes a été examinée 6 heures après l’application de la dose thérapeutique. En même temps, l’incorporation de la radioactivité dans les phospholipides (céphaline, lécithine, sphingomyéline) des leucocytes mis sous l’incubation, a été comparée avec les valeurs observées in vivo chez le même malade. On a trouvé une correspondance assez favorable de ces deux valeurs.Der Einbau der Radioaktivität aus P32-Orthophosphat in Phospholipide von Leukozyten wurde in vivo und in vitro bei Patienten mit Leukämie untersucht. Blutproben, die vor der Verabreichung einer therapeutischen P32-Dosis abgenommen worden waren, wurden mit einer Menge von P32 inkubiert, die gleich jener war, die im Kreislauf 30 Minuten nach der intravenösen Injektion der Therapiedosis gefunden wurde.Die Verteilung der Radioaktivität in den Phospholipidfraktionen der Leukozyten wurde 6 Stunden nach der Verabreichung der therapeutischen Dosis untersucht. Gleichzeitig wurde der Einbau der Radioaktivität in die Leukozyten-phospholipide (Cephalin, Lezithin, Sphingomyelin) in den inkubierten Blutproben der gleichen Patienten verglichen mit den Werten, die in vivo beobachtet wurden.Zwischen den In-vivo- und den In-vitro-Verteilungen in den Hauptfraktionen der Leukozytenphospholipide wurde eine recht gute Übereinstimmung beobachtet.